Contribution of university extension activities in a group of pregnant women and couples for the training of nurses - Margarete Maria de Lima; Mayara Leal Machado; Roberta Costa; Bruna Canever; Juliana Coelho Pina; Isadora Ferrante Boscoli de Oliveira Alves (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To understand how the participation of nursing students with a group of pregnant women and couples contributes to their training and professional practice. Method: Qualitative, descriptive and exploratory study. Data were collected using individual and semi-structured interviews held in 2017 with nursing students holding scholarships for extension work and working with a group of pregnant women and couples, implemented in a university hospital in the south of Brazil. The interviews were recorded and analyzed using Minayo's operational proposal. Results: The analysis revealed the reasons nursing students applied for a position in the extension project; the perceptions they held of the group of pregnant women; and how their experience with this extension project contributed to their academic and professional lives. Conclusion: The extension project positively impacts the lives of students, assisting both with curricular subjects and after graduation.